MOLECULAR DYNAMIC SIMULATION STUDY ON ADMISSIBILITY OF GREEN ADDITIVES IN HYDRAULIC FRACTURING FLUID - Azlan, Alissa binti Azlan (Universiti Teknologi Petronas, 2021)
This study focuses on interactions between fluid-fluid phase in hydraulic fracturing between a mixture of water and green surfactant used in this study, D-limonene, with methane gas in shale gas reservoir.